Titanium-catalyzed transesterification as a route to the synthesis of fully biobased poly(3-hydroxybutyurate-co-butylene dicarboxylate) copolyesters, from their homopolyesters. (May 2017) - Debuissy, Thibaud; Pollet, Eric; Avérous, Luc
Graphical abstract: Highlights: Synthesis of PHB-based copolyesters via the titanium-catalyzed transesterification process. Tunable macromolecular architectures according to reactions conditions. Good thermal stability of copolyesters. Crystalline structures and thermal properties highly dependent on the macromolecular architecture. Possibility to synthesize copolyester with higher HB content than with the enzymatic process. Abstract: Fully biobased poly(3-hydroxybutyrate- co -butylene adipate) (poly(HB- co -BA)) and poly(3-hydroxybutyrate- co -butylene succinate) (poly(HB- co -BS)) copolyesters were synthesized by transesterification between small chain length PHB and poly(butylene dicarboxylate)s (PBS or PBA) with different molar masses, different HB/BA (or HB/BS) molar ratios, in solution or in bulk, using titanium (IV) isopropoxide (TTIP) as an effective catalyst. All synthesized copolyesters were fully characterized by different chemical and physicochemical techniques including NMR, SEC, FTIR, WAXS, DSC and TGA. The influence of (i) the reaction process (ii) the nature of poly(butylene dicarboxylate) used, (iii) the molar masses of the starting homopolymers, (iv) the reaction temperature, (v) the catalyst amount and (vi) the HB/BS (or HB/BA) molar ratio on the transesterification reaction and copolyester properties were investigated. The transesterification in bulk with 1 mol.% of TTIP at 175 °C from low molar mass starting homopolyesters permitted to quickly obtain random copolyesters with final composition similar to the feeds and without thermal degradation. Random poly(HB-co-BA) copolyesters were amorphous at room temperature, whereas poly(HB- co -BS) copolyesters melted at temperatures higher than 40 °C. Poly(HB- co -BS) copolyesters exhibited only a PBS crystalline phase, except for copolyesters with a low degree of randomness and a significant HB content. The melting and crystallization temperatures as well as their respective enthalpies decreased with the randomization and the HB content.